Current Considerations in the Management of Positional Plagiocephaly [Consideraciones Actuales en el Abordaje de la Plagiocefalia Posicional] - Imperatore-Dupre, M (Sociedad Chilena de Pediatria, 2023)
Since the American Academy of Pediatrics recommended the supine sleeping position for infants to prevent SIDS, positional plagiocephaly (PP) prevalence has increased. There are great controversies regarding the possible consequences of PP and the degree of severity required for them to manifest. There is no consensus on the efficacy of PP therapies, such as positioning, kinesiology, and cranial orthoses. This review aims to analyze the existing literature to update the causes, main characteristics, and evidence on the treatment of PP. Intervention from the newborn period is important, encompas-sing both prevention and management education, as well as early screening, evaluating the possible presence of congenital muscular torticollis, to start early treatment. The presence of PP can be a risk marker for psychomotor development. © 2023, Sociedad Chilena de Pediatria. All rights reserved.